2017
DOI: 10.1037/pag0000157
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous or intentional? Involuntary versus voluntary episodic memories in older and younger adults.

Abstract: Involuntary episodic memories are memories of past events that come to mind with no preceding attempt of retrieval. Such memories have received little attention in relation to aging compared with voluntary episodic memories (i.e., intentionally retrieved memories of past events). It is well documented that older compared with younger adults have reduced access to episodic memories, when retrieval is voluntary, but little is known about their involuntary episodic recall. Recent evidence suggests that involuntar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 58 publications
9
22
0
Order By: Relevance
“…However, the prospective bias was present for a significant minority of deliberate taskunrelated thoughts, suggesting that the prospective bias in mind-wandering studies could be at least partly explained by instances of intentional mind-wandering about the future (Seli et al, 2016). Taken together, findings from these two studies using laboratory and naturalistic methods appear to be replicating the results of Berntsen et al (2017) on involuntary autobiographical memories, which also showed that older adults did not differ from young participants in the number of reported involuntary autobiographical memories in the laboratory (Study 1) and in everyday life (Study 2).…”
Section: Development Across the Life Spansupporting
confidence: 51%
See 1 more Smart Citation
“…However, the prospective bias was present for a significant minority of deliberate taskunrelated thoughts, suggesting that the prospective bias in mind-wandering studies could be at least partly explained by instances of intentional mind-wandering about the future (Seli et al, 2016). Taken together, findings from these two studies using laboratory and naturalistic methods appear to be replicating the results of Berntsen et al (2017) on involuntary autobiographical memories, which also showed that older adults did not differ from young participants in the number of reported involuntary autobiographical memories in the laboratory (Study 1) and in everyday life (Study 2).…”
Section: Development Across the Life Spansupporting
confidence: 51%
“…Currently, evidence in relation to age effects on involuntary cognitions is mixed (for a review, see Maillet & Schacter, 2016), with studies of involuntary autobiographical memories showing small age effects (e.g., Schlagman, Kliegel, Schulz, & Kvavilashvili, 2009) or the absence of age effects (Berntsen, Rasmussen, Miles, Nielsen, & Ramsgaard, 2017) when comparing the number and characteristics of reported involuntary memories in young and old participants in the laboratory and everyday life (see also Gardner & Ascoli, 2015). In contrast, research on mind-wandering has resulted in significant negative age effects by showing that older adults report fewer instances of task-unrelated thoughts when engaged in vigilance or reading tasks (for reviews of these studies, see Jordão et al, 2019;Maillet & Schacter, 2016).…”
Section: Development Across the Life Spanmentioning
confidence: 99%
“…However, other studies using retrospective questionnaires (Berntsen & Rubin, 2002;Berntsen, Rubin, & Salgado, 2015;Moulin et al, 2014) reported no age-related differences. In a very recent line of studies, Berntsen, Rasmussen, Miles, Nielsen, and Ramsgaard (2017) examined involuntary memories in young and older adults in a laboratory setting (i.e., involuntary memories of a film of a simulated event) and during a normal day in their life. Across both studies, no significant age differences in the frequency of involuntary memories were found.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in contrast to laboratory findings of mindwandering that are based on attentionally demanding vigilance or Go/No-Go tasks (which show negative age effects), the effects of age on experiencing spontaneous future or past thoughts in everyday life should be absent or less pronounced (cf. Berntsen, Rasmussen, Miles, Nielsen, & Ramsgaard, 2017). The inhibitory theory of ageing by Hasher and colleagues (Hasher et al, 1979;Hasher & Zacks, 1988), however, predicts that due to increased distractibility in response to irrelevant stimuli, older adults should experience higher rates of task-unrelated thoughts, which is more in line with Gardner and Ascoli (2015) findings of higher rates of future thoughts in older than younger adults.…”
Section: Absence Of Age Effects On Spontaneous Past and Future Thinkimentioning
confidence: 95%
“…Indeed, preserved spontaneous cognitive processes in everyday life may have functional value in supporting the organisation of daily activities and effective execution of plans, hence contributing to the efficient and successful functioning of older adults at home or in the workplace (cf. Berntsen et al, 2017).…”
Section: Absence Of Age Effects On Spontaneous Past and Future Thinkimentioning
confidence: 99%